1983
DOI: 10.1104/pp.73.1.1
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Measurement of Indole-3-acetic Acid Decarboxylation in Aging Coleus Petiole Sections

Abstract: The concentration of indoleacetic acid (IAA) in plant tissues is regulated, in part, by its rate of decarboxylation. However, the commonly used in vitro assays for IAA oxidase may not accurately reflect total in vivo decarboxylation rates. A method for measuring in vivo decarboxylation was utilized in which '4CO2 is collected following uptake of IAA is usually found in highest concentration in the juvenile parts of the plant, and at lower levels in regions removed from the growing points (10) and in the older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Thus, the idea proposed by Galston and Dalberg in 1954 that increased IAA-oxidase might account for the decreased IAA level in older, non-growing tissues has long been accepted. However, several studies have reported higher 1AA-oxidase in younger growing tissues which also exhibited higher IAA concentrations (Rajagopal and Larsen 1974;Brennan and Jacobs 1983;Valpuesta et al 1989;Sfinchez-Bravo et al 1989). Though a compartmentalization of IAA and IAA-oxidase might explain these results, the presence of a high IAA concentration in tissues with a high capacity to destroy IAA would agree with the proposed hypothesis that IAA must be destroyed following "the growth promoting act" (Cohen and Bandurski 1978).…”
Section: Introductionsupporting
confidence: 74%
“…Thus, the idea proposed by Galston and Dalberg in 1954 that increased IAA-oxidase might account for the decreased IAA level in older, non-growing tissues has long been accepted. However, several studies have reported higher 1AA-oxidase in younger growing tissues which also exhibited higher IAA concentrations (Rajagopal and Larsen 1974;Brennan and Jacobs 1983;Valpuesta et al 1989;Sfinchez-Bravo et al 1989). Though a compartmentalization of IAA and IAA-oxidase might explain these results, the presence of a high IAA concentration in tissues with a high capacity to destroy IAA would agree with the proposed hypothesis that IAA must be destroyed following "the growth promoting act" (Cohen and Bandurski 1978).…”
Section: Introductionsupporting
confidence: 74%
“…In contrast, after a 2-h lag, the decarboxylative capacity of green discs increased in a linear manner and 24h after excision > 60% of the [I'-14C]IAA absorbed by the discs was subjected to decarboxylation during the subsequent 1-h incubation. The development of the IAA-decarboxylative capacity after excision of the immature green pericarp discs is suggestive of the involvement of wound-induced increases in peroxidases that are associated with repair processes in a number of tissues (Brennan and Jacobs 1983;Lagrimini and Rothstein 1987;Svalheim and Robertsen 1990). The lack of a similar increase in the IAA-decarboxylation capacity of the more-mature breaker and pink discs is in keeping with the lower increases in peroxidase activity that are reported to occur after the wounding of older tissues (Birecka et al 1976;Macheix et al 1986).…”
Section: Resultsmentioning
confidence: 58%
“…For the HPLC analysis the seedlings were treated with a double isotope solution containing 1,539 Bq (0.19pM) of [5-3H]-IAA + 781 Bq (42.2pM) of [l-l4 Cl-IAA. At different times the apical first cm of the hypocotyls was divided into sections of 0.5cm length (for better extraction they were cut in half longitudinally) and extracted according to Brennan and Jacobs [3] with the following modifications: 0.5 ml acetonitrile/l cm section, 48 h at 4°C in darkness. Treated plants were individually analyzed either by TLC or HPLC.…”
Section: Decapitated Seedlingsmentioning
confidence: 99%
“…Frequently, oxidative degradation of IAA implies decarboxylation [3,141, IAI, HMOx, IM and BIM being the major products of this route [2,9,11,12,15,19,24,30,331. Alternatively, a non-decarboxylative pathway producing oxindole-3-acetic acid-like compounds has been reported [IO, 16,201.…”
Section: Introductionmentioning
confidence: 99%